2006
DOI: 10.1007/s10658-006-9063-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced mycotoxin production of a lipase-deficient Fusarium graminearum mutant correlates to toxin-related gene expression

Abstract: Fusarium graminearum causes important diseases of small-grain cereals and maize and produces several mycotoxins. Among them, deoxynivalenol (DON) and zearalenone (ZEA) can accumulate in feedstuffs and foods to health-threatening levels. Although DON is important for fungal virulence in wheat, disease severity in the field does not correlate with mycotoxin concentrations. We compared gene expression and mycotoxin production of lipase-deficient mutants (Dfgl1), strongly reduced in virulence, and the respective w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 27 publications
(44 reference statements)
0
22
0
Order By: Relevance
“…Grounded mycelium of F. graminearum WT was used as standard. Isolated DNA served as template in qPCR (Voigt et al, 2007) using b-tubulin primers 15 and 16 (Table 1). By calculating the number of b-tubulin gene copies per milligram mycelium of the standard and considering a 50% weight loss of dried inoculated spikelets, determination of milligram mycelium per kilogram ground sample was possible.…”
Section: Deoxynivalenol (Don) Measurementmentioning
confidence: 99%
“…Grounded mycelium of F. graminearum WT was used as standard. Isolated DNA served as template in qPCR (Voigt et al, 2007) using b-tubulin primers 15 and 16 (Table 1). By calculating the number of b-tubulin gene copies per milligram mycelium of the standard and considering a 50% weight loss of dried inoculated spikelets, determination of milligram mycelium per kilogram ground sample was possible.…”
Section: Deoxynivalenol (Don) Measurementmentioning
confidence: 99%
“…Consequently, Tri5 is an attractive target for mutagenesis (2,36) and for molecular detection of trichothecene-producing Fusarium spp. (22,34,38,44,47). Several studies have focused on Tri5 expression to unravel specific aspects of the F. graminearum-host interaction.…”
mentioning
confidence: 99%
“…These observations may suggest that aurofusarin pigment, unlike DON, is a constitutive part of the fungus, possessing no toxic effect to the fungus itself. It could be that F. graminearum produced aurofusarin to inhibit the growth of other microorganisms (Medentsev et al 1993) and to antagonize competing organisms during saprophytic growth phase (Voigt et al 2007). …”
Section: Resultsmentioning
confidence: 99%
“…Lysoe et al (2006) found the mutant with the deletion of aurofusarin gene cluster did not show decreased pathogenicity in barley seedling. Voigt et al (2007) proposed that F. graminearum produced polyketides including aurofusarin to antagonize competing organisms during saprophytic growth phase.…”
Section: Introductionmentioning
confidence: 99%